Uang Virtual (Cryptocurrency) sebagai Sarana Tindak Pidana Pencucian Uang dalam Perdagangan Saham - Dewanti Arya Maha Rani; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Jurnal Konstruksi Hukum, 2021)
The continuation of the electronic media that is widely discussed today is virtual money, commonly known as cryptocurrency. Cryptocurrency can also be referred to as an unformed commercial object; actually in digital form which can be used in electronic transactions. This study aims to analyze the existence of virtual money (cryptocurrency) in stock trading in Indonesia and to find out the responsibilities of money laundering offenders who use virtual money (cryptocurrency) in stock trading. The research method used is normative legal research. The results show that the existence of virtual money (cryptocurrency) in stock trading in Indonesia when used as currency unification, transact, trade or as a means of payment with businesses in this case, especially stock trading in Indonesia can be said to be invalid in terms of Law Number 7. 2011 concerning Currency. Users of virtual money (cryptocurrency) in Indonesia are quite widely used in business, which can be seen in Indonesia itself that virtual money (cryptocurreny) such as Bitcoin and Centcoin are circulating. Then, the responsibility of the perpetrators of money laundering who use virtual money (Cryptocurrency) in stock trading, where this action has a very negative impact on the Indonesian State, especially in terms of business because people who have committed these crimes take advantage of technological advances unwise so that the perpetrators can be ensnared based on Law No. 8 of 2010 concerning the prevention and eradication of the crime of money laundering.